2012
DOI: 10.1590/s0034-89102012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental lead poisoning among children in Porto Alegre state, Southern Brazil

Abstract: OBJECTIVE:To estimate the prevalence of lead poisoning in children and to identify associated factors, as well as possible local sources of contamination. METHODS:A cross-sectional prevalence study conducted in 2006 with a random sample of 97 children age zero to fi ve years from a neighborhood in Porto Alegre, Southern Brazil. Blood lead levels were measured and a questionnaire administered to collect information on sociodemographics, recycling and dwelling. A preliminary environmental evaluation was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…There were 13 studies of children living in the neighborhood of leadcontaminated areas in the northeast region, [80][81][82][83][84][85][86][87] the southeast region (State of Sao Paulo), [88][89][90][91] and the south region (State of Rio Grande do Sul). 92 One study was done in an area contaminated with aluminum 93 and another in an area contaminated with arsenic. 94 In all of these studies, the distance between the place of residence and the pollution source was correlated with levels of metal in the children.…”
mentioning
confidence: 99%
“…There were 13 studies of children living in the neighborhood of leadcontaminated areas in the northeast region, [80][81][82][83][84][85][86][87] the southeast region (State of Sao Paulo), [88][89][90][91] and the south region (State of Rio Grande do Sul). 92 One study was done in an area contaminated with aluminum 93 and another in an area contaminated with arsenic. 94 In all of these studies, the distance between the place of residence and the pollution source was correlated with levels of metal in the children.…”
mentioning
confidence: 99%
“…Aunque no hay publicaciones sobre la presencia de plomo y cadmio en agua, alimentos y peces en la región de La Mojana, las concentraciones de estos metales encontradas en la sangre de sus habitantes pueden estar relacionadas con la ingestión de aguas y alimentos contaminados (44,45). Probablemente, esto es consecuencia de dos procesos: en primer lugar, las constantes inundaciones provenientes del río Cauca, el cual recoge desechos tóxicos con presencia de estos metales generados por la actividad minera e industrial a lo largo de su recorrido (46) que son drenados a la zona, contaminando las aguas, los suelos y los alimentos.…”
Section: Discussionunclassified
“…Curvo [125] analyzed the positive prevalence of morbimortality due to cancer in adolescents in cities of the CO region, where there was an increase in grain harvesting and 48.91% of agrochemicals used were shown to be carcinogenic. [129] to estimate the prevalence of lead poisoning in children and to identify associated factors, as well as possible local sources of contamination crosssectional 16% blood lead levels ≥ 10.0 μg/dL 0 -5 y S male gender; age: 2,6 y; waste recylcing activities. ; soil, and air pollution.…”
Section: A Study On Incidence Of Clinical Hypoxic Ischemic Encephalopmentioning
confidence: 99%
“…Concerning the prevalence of lead poisoning, studies found blood lead levels ≥ 10.0 μg/dl, in children, associated with waste recycling [129] and residing close proximity to a battery factory [136]. Another study showed a strong association between adolescents with high dental enamel lead levels living in or close a contaminated area [131].…”
Section: Grandjean Et Almentioning
confidence: 99%